PENGARUH LIMBAH CANGKANG KERANG SEBAGAI SUBSTITUSI AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Syafiadi Rizki Abdillah; Sahrul Zulfikar; Yonas Prima (Fakultas Teknik Universitas Krisnadwipayana, 2023)
The development of concrete technology in trials of adding mixed ingredients continues to be carried out to obtain the desired strength and quality of concrete. The clam shells contain pozzolanic chemical compounds, namely lime which is expected to be used as a substitute for fine aggregate in a mixture of concrete constituents. This research was conducted to determine the compressive strength of concrete by utilizing shell waste as a substitute for fine aggregate of 0%, 15% and 25% with aging observed at 7, 14 and 28 days. This research carried out several material tests such as sieving, aggregate specific gravity, moisture content, silt content, wear and tear, organic matter, slump test and concrete compressive strength test. Based on the results of the study, it was found that the optimum strength in mixed variations with shell waste as a substitute for 15% fine aggregate obtained a compressive strength value of 14.09 MPa at 14 days. From the results of the research conducted, it can be concluded that the use of shell waste as a substitute for fine aggregate is not recommended for the manufacture of concrete in the world of construction, because the strength value of the concrete obtained does not meet the requirements of Standard SNI 7656: 2012